Implementasi Kurikulum Merdeka Belajar dalam Menumbuhkan Karakter Religius di Madrasah Tsanawiyah Diponegoro dan Madrasah Tsanawiyah Sudirman - Hanif Aniqo Rois; Mukh Nursikin (Attractive : Innovative Education Journal, 2024)
The purpose of this study is 1) To find out the planning of the independent learning curriculum in fostering religious character at MTs Diponegoro and MTs Sudirman Kawengen, East Ungaran District, Semarang Regency. 2) To find out the implementation of the independent learning curriculum in fostering religious character at MTs Diponegoro and MTs Sudirman Kawengen, East Ungaran District, Semarang Regency. This study uses a qualitative research method with a field research approach. The subjects in this study were the head of the madrasah, teachers and students. Data collection techniques were obtained through observation, interviews, and documentation. The results of the study are, 1) Independent Learning Curriculum Planning in Cultivating Religious Character at MTs Diponegoro, namely, Analyzing Learning Achievements, Planning and implementing diagnostic assessments, meaning that diagnostic assessments aim to identify the competencies, strengths, and weaknesses of students. While the planning at MTs Sudirman Kawengen is to prepare the Operational Curriculum of the Education Unit (KOSP) document, prepare the flow of learning objectives, compile criteria for achieving learning objectives, compile teaching modules and prepare Pancasila profile projects. 2) Implementation of the independent curriculum implementation of Islamic Religious Education Subject Teachers at MTs Diponegoro in participating in the Training is fairly sufficient (needs improvement).